When trade unions turn to litigation: 'getting all the ducks in a row'. Issue 3 (8th June 2018) - Guillaume, Cécile
Abstract: Driven by their members' demands and the need to adopt more combative legal strategies in order to oppose the deterioration of working and employment conditions, British trade unions have developed in‐house legal expertise and supported many individual and multiple claims. This article investigates the variation in unions' legal practices and examines their organisational responses to law and the role of compliance professionals in the regulation of employment litigation. It provides a nuanced account of the influence of legal rationality on the framing of union strategies and shows that, under certain conditions, trade unions are able to build multi‐pronged tactics by using litigation as a complement to other forms of action.